ComViver Online application: development of a digital intervention to regulate adolescents’ behavior in cyberbullying events - N. Pereira; S. Oliveira; P. Paulino; P. Ferreira; H. Rosa; R. Ribeiro; J. P. Carvalho; L. Coheur; I. Trancoso; A. M. Veiga Simão (ticEduca 2018 — V Congresso Internacional TIC e Educação, 2018)
This communication aims to present the phases of development of a digital intervention to help adolescents regulate their behavior through language in situations of cyberbullying.The design of the application ComViver Online (PTDC/MHC/PED/3297/2014) includes the following stages: 1) identifying and categorizing potential aggressive language used online by adolescents; 2) developing the application methodology and content, and testing it with adolescents; 3) implementing and evaluating the application in schools; and 4) analyzing case studies to understand how adolescents regulate their behavior. In the first phase, qualitative data was collected from 1,607 5th to 12th grade students (Mage = 15.1, SD = 2.27) studying in Portugal. The aim was to evaluate the language used by adolescents in situations of cyberbullying. Firstly, propositions were evaluated through content analysis using NVivo software. The results yielded identification of verbal written expressions used by adolescents according to different cyberbullying behavior (e.g., threatening, harassing, insulting). Secondly, an annotation process was conducted of public tweets in Portugal to identify aggressive language and conflicts and/or attacks. These findings allowed the development of a methodology to detect potential cyberbullying situations. In the second phase, content related with cyberbullying was developed and included in the application (e.g., informational content, self-questioning strategies, verbal communication skills) along with the previous methodology. A prototype of the application was then tested with a group of adolescents (N= 21). In the third phase, a roadmap for implementation, as well as session plans were conducted. A quasi-experimental study with experimental and different control conditions with 9th graders from a group of schools in the Metropolitan Area of Lisbon (N=220) is currently being conducted. The final phase will include a three-month data collection of case studies to understand how adolescents regulate their behavior while using the application ComViver Online.